2012
DOI: 10.1089/cyber.2012.0169
|View full text |Cite
|
Sign up to set email alerts
|

Its ovr b/n u n me: Technology Use, Attachment Styles, and Gender Roles in Relationship Dissolution

Abstract: Relationship dissolution now occurs through technologies like text messaging, e-mail, and social networking sites (SNS). Individuals who experience relationship dissolution via technology may differ in their attachment pattern and gender role attitudes from those who have not had that experience. One hundred five college students (males=21 and females=84) completed an online questionnaire about technology-mediated breakups, attachment style, and gender role attitudes. More than a quarter of the sample had expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…In this study Chat/IM was the most frequent method of delivery of the breakup. This is different than results found with the American sample in the study by Weisskirch and Delevi (2012) where participants were found to be more likely to use text messaging. Participants indicated that chat/IM was most acceptable for breaking up whereas the preferred means for the US sample was voicemail.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study Chat/IM was the most frequent method of delivery of the breakup. This is different than results found with the American sample in the study by Weisskirch and Delevi (2012) where participants were found to be more likely to use text messaging. Participants indicated that chat/IM was most acceptable for breaking up whereas the preferred means for the US sample was voicemail.…”
Section: Conclusion and Discussioncontrasting
confidence: 99%
“…In order to measure participants' experience of being broken up with via technology, use of technology to break up and acceptability of using technology to break up these questionnaires were used which are described below. The questionnaires were developed by Weisskirch and Delevi (2012) and were translated into Turkish for the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one could also study the more intricate relationship between technology use and personal relationships. Weisskirch, et al [43] look at the attachment styles of couples involved in a relationship breakup online. It is the only work that we are aware of that looks at the act of breaking up through technology.…”
Section: Related Workmentioning
confidence: 99%
“…It is estimated that more than 85% of Americans [2] go through this process at least once in their life time. Correspondingly, lots of research in psychology and other fields has investigated relationship breakups, looking at dimensions such as the impact of breakups on mental health [34], post-breakup personal growth [40], or the increased use of technology for the actual act of breaking up [43].…”
Section: Introductionmentioning
confidence: 99%